An evaluation of the Unciano Colleges of Antipolo Academic Health Library Collection and Services based on users' assessment - Santos, Vladimir Ross C. (School of Library and Information Studies, University of the Philippines Diliman, 2008)
Since an academic health library functions as a vital unit for the continuing education of students and faculty members, a deep analysis of its collection and services has to be done in order to make the necessary changes to meet the library users' demands. It is in this direction that this study focused on the evaluation of the collection and services based on users' assessment of the Unciano Colleges of Antipolo Academic Health Library.